If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0 = 6t + 3(2 + 9t) + 7 0 = 6t + (2 * 3 + 9t * 3) + 7 0 = 6t + (6 + 27t) + 7 Reorder the terms: 0 = 6 + 7 + 6t + 27t Combine like terms: 6 + 7 = 13 0 = 13 + 6t + 27t Combine like terms: 6t + 27t = 33t 0 = 13 + 33t Solving 0 = 13 + 33t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-33t' to each side of the equation. 0 + -33t = 13 + 33t + -33t Remove the zero: -33t = 13 + 33t + -33t Combine like terms: 33t + -33t = 0 -33t = 13 + 0 -33t = 13 Divide each side by '-33'. t = -0.3939393939 Simplifying t = -0.3939393939
| x+9+5x=21x+2x | | y=-5+3x-2x^2 | | -6k+2k+10=-2(k-3)+4 | | 3/4(m)=-5/6 | | x=zy | | 3x-12-6-4x=3+12x-20 | | y=-2x^2+5x+12 | | =3+5(5t+1)+8t | | a+0.45=1.29 | | x^2-8x+16-y^2=0 | | 40-10t=66+16t | | 12n+5=3+32 | | 0.75n+100=0.25n | | -2(3x+5)=x-5(3-x) | | -4s+8= | | 123-6x=12x+17 | | 3f-12=-13 | | 6m=96 | | (2x+1)+(3x-31)=180 | | -2=4r | | -4n-3=-2(6+5n)+6(n-7) | | 5.7+(14.2-9.4)*9.9= | | Y(-2)=5(-2)(2)-7 | | 2x^3+7x^2-10x-5=0 | | -8x^2+7x+8=0 | | -12-5=8-10x | | -9(1-6p)+3(2-4p)= | | Y(-2)=5(-4)-7 | | -8x^2+7+8=0 | | 5(2x-3)-2(x+4)= | | -8x^2+8x+9=0 | | -13-(-10)= |